A Al-Jabiri's Epistemological Critique of Kufr in Tafsir Al-Misbah: Implications for Transforming Islamic Contemporary - Dasim, Dasim; Syifa Amin Widigdo (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study uses Mohammed Abed Al-Jabiri's framework of Arab reason critique to critically analyze the epistemological construction of kufr (disbelief) in M. Quraish Shihab's Tafsir Al-Misbah. This study examines the hermeneutical techniques and epistemological justifications that underlie Shihab's interpretation of kufr-related verses using a qualitative library research methodology. The results show that Shihab's interpretation dialectically shifts toward Burhani epistemology, which is marked by logical and moral reasoning, even if it is based on Bayani epistemology, which is focused on textual authority and linguistic analysis. His inclusive, contextual interpretation that combines social plurality with religious purity is one way that this metamorphosis is demonstrated. By illustrating the potential epistemological growth within Islamic reasoning, the research theoretically advances Qur'anic hermeneutics. Practically, it advances Islamic by suggesting curriculum reform based on epistemological plurality. The study highlights how tolerance, pluralism, and religious moderation are encouraged in contemporary Islamic when kufr is understood within an open, critical, and contextual framework. In order to create inclusive and transformational pedagogical models in Muslim al institutions, it is imperative that Bayani and Burhani epistemologies be integrated.